Implicatioan of Training and Career Development Program on Worker Performance at Bank Republik Indonesia Syariah Kc Madiun - Anggara, Ricko; Veithzal Rivai Zainal; Lenny Christina Nawangsari (Dinasti International Journal of Digital Business Management, 2023)
One of the factors to improve human resources in the company or agency is conducting training which supported by career development to employees in order to defeat competition between companies, when human resources functions are in high quality; the output will be in maximum performance. Training is a comprehensive step of the company to develop the ability of individuals, groups, knowledge or attitudes which gained to change employee behavior in order to achieve predetermined goals. Career development is a sequence step taken by a person by making personal efforts with the aim of achieving career planning that has been set in accordance with the implementation of the field. Employee performance is a result of someone's activities in the organization. The aim of this paper is to see any impacts of training and career development on worker performance at Bank BRI Syariah KC Madiun. The population in this study is ‘workers’ of Bank BRI Syariah KC Madiun. The total sample in this study was all employees of Bank BRI Syariah KC Madiun as many as 42 respondents using total sampling (census). Data collection techniques in this study are literature, observations, interviews and dissemination of questionnaires. The analytical techniques used in this study are quantitative descriptive analysis and multiple linear repression analysis. The techniques of this study are training (X1,) and career development (X2) which have positive influence and have significance employee performance (Y) at Bank BRI Syariah KC Madiun.